PENENTU KEUNGGULAN BERSAING: PERAN PEMASARAN LANGSUNG DAN KUALITAS PRODUK: Studi Pada Perusahaan Gorong - Gorong di Kota Banjar dan Ciamis - Qolbi, Nur; Darna, Nana; Abdul Kader, Mukhtar (Perwira Journal of Economics & Business, 2022)
The need for facilities and facilities in Banjar and Ciamis cities, there are entrepreneurs who open a culvert making business. The covid-19 outbreak has caused culvert sales to decline. Thus culvert companies are required to choose and establish strategies that can be used to deal with competition. The purpose of this study is to analyze the determinants of competitive advantage in culvert companies in Banjar and Ciamis Cities. This research was conducted in a survey by examining 65 consumers of culvert companies in Banjar and Ciamis cities and analyzed using multiple correlations. The results showed that direct marketing and product quality have a positive effect on competitive advantage